Decoupling economy from natural resources consumption and environmental pressure: analysis of Kazakhstani case - Kalmakova, D. T.; Moldabekova, A. T.; Amangeldiyeva, B. A. (Journal of Economic Research & Business Administration, 2023)
Economic development has always been associated with a rise in the use of natural resources as well as an increase in environmental degradation. However, responsible production principles suggest the opposite. The need to separate economic growth from the consumption of limited natural resources and increasing environmental degradation gave rise to the concept of decoupling. The concept is highly relevant for achieving sustainable economic growth while diminishing the use of resources and simultaneously creating positive environmental impacts. This article aims to analyze the current decoupling state of the kazakhstani economy from natural resources consumption and environmental impact as well as decoupling trends over a certain period. The research was conducted in two stages: (1) statistical analysis of the resource decoupling in Kazakhstan on key natural resources (water, energy) as well as impact decoupling from such indicators as ecological footprint, waste generation, and emissions; (2) a regression model for evaluating dependence of economic growth in Kazakhstan on the consumption of natural resources and environmental degradation. The data was collected for the period from 2010 to 2021. The results show that economic growth in Kazakhstan is accompanied by an increase in waste generation, and emissions into the environment, in particular emissions of liquid and gaseous pollutants. This is in line with previous research which also didn’t reveal the effect of decoupling from pollutants emissions. However, there was revealed an absolute decoupling from freshwater resources as well as a tendency for absolute decoupling from energy resources consumption. These findings can be used to define the current decoupling state and trends in Kazakhstan to monitor the effectiveness of the application of responsible production principles and the achievement of sustainable development goals. Key words: decoupling, economic growth, resources consumption, environmental impact, responsible production.